Penerapan Model Pembelajaran Menyenangkan (Joyfull Learning) dalam Meningkatkan Hasil Belajar IPA - Muqtakdir Nurfalaq; Ninah Wahyuni; Mohammad Mulyadi Prasetyo; Sitti Wirda; Nurhidayah Nurhidayah (Jurnal Biotek, 2022)
This study aimed to describe an improvement in science learning outcomes with applied a joyful learning model for class VIII students at SMP Negeri 25 Cenrana. This study was a Classroom Action Research (CAR) conducted on 25 students in SMP Negeri 25. The subjects consisted of 14 female students and 11 male students. Data was gathered using observational methods and learning outcomes assessments, and then processed through a descriptive and statistical analysis. The results showed that the average value of learning outcomes in the first cycle was 62.6 and improved in the second cycle to 83.2. Students who completed their learning outcomes in the first cycle were eight, or 32%, and in the second cycle it became 92%. It appears that there was an improvement in the learning outcomes of science students in class VIII of SMP Negeri 25 Cenrana by applying the joyful learning model.